WHEN SELF BELONGING AND ORGANIZATION CULTURE COLLIDE - Masyhuri, Mohammad Ali; Emmywati; Purnomo, Teguh; Suprihandari, Miya Dewi (Transpublika Publisher, 2023)
Organizations and institutions serve as dynamic hubs where diverse backgrounds and perspectives converge. While individuals often establish deep connections, considering these places a second home. This study explores how personal diversity, technology, and organizational culture intersect in organizations, aiming to understand their impact on self-belonging and the overall culture. Through literature review and case analysis, we scrutinize the intricate relationships between personal diversity, technology, and culture. Effective management can alleviate challenges stemming from these dynamics, enhancing human resource conditions. Successful strategies embracing diversity and technology can positively influence these conditions. Although technology accelerates institutional development, cultural change is gradual. Effective management is crucial in bridging gaps between personal diversity, technology, and cultural continuity. Improved conditions foster self-belonging, enriching organizational culture. This research underscores the role of strategic management in harmonizing personal identities with organizational values, ultimately fostering an adaptive institutional culture.